Merawat Mistisisme di Surakarta - Novia Wahyu Wardhani; Erisandi Arditama; Wahyudin Noe; Sabar Narimo (Universitas Andalas, 2021)
Since the days of kingship-kingdoms in Indonesia, Java, especially Surakarta, has been attached to something mystical. This has to do with forces beyond human power. This behavior exists because that power can have a positive impact. Examples can perpetuate power, bring authority, attract fortune, and attract. But interestingly, at that time mystical behavior was hidden while in this modern and democratic era mysticism was packaged in a different form. This research is qualitative research with an ethnographic approach that focuses on the peculiarities of mysticism in the city of Surakarta in 2019-2020. The data collected comes from the first observations made in Surakarta. Second, interviews with mystical actors. Third, documentation obtained from books, journals, and mass media explaining mysticism in Surakarta. The data validity uses the triangulate method, member check, prolonged time, peer debriefing. Data analysis using ethnographic analysis model. The result is that the people of Surakarta, especially government leaders and those with an interest in maintaining mysticism by making mystical traditions become cultural preservation, are legally regulated in policy, the implementation of traditional rituals is open so that people participate, and make irrational ones rational.